Capital Flow Data : A Guide for Empirical Analysis and Real-time Tracking - Koepke, Robin (IMF Working Papers; Working Paper ;, 2020)
This paper provides an analytical overview of the most widely used capital flow datasets. The paper is written as a guide for academics who embark on empirical research projects and for policymakers who need timely information on capital flow developments to inform their decisions. We address common misconceptions about capital flow data and discuss differences between high-frequency proxies for portfolio flows. In a nowcasting 'horse race' we show that high-frequency proxies have significant predictive content for portfolio flows from the balance of payments (BoP). We also construct a new dataset for academic use, consisting of monthly portfolio flows broadly consistent with BoP data.